2016
DOI: 10.1186/s12884-016-1095-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with use of herbal medicines during pregnancy among women attending postnatal clinics in Gulu district, Northern Uganda

Abstract: BackgroundAccording to World Health Organization (WHO) estimates, 80 % of the population living in rural areas in developing countries depends on traditional medicine for their health needs, including use during pregnancy. Despite the fact that knowledge of potential side effects of many herbal medicines in pregnancy is limited and that some herbal products may be teratogenic, data on the extent of use of herbal medicines by women during pregnancy in the study setting is largely unknown. We determined the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
82
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 26 publications
16
82
4
2
Order By: Relevance
“…These results are similar to those obtained by Aka et al in 2016 in Ivory Coast (100% 3rd trimester) [24], Kamatenesi et al 2007 in Uganda (91% in the 3rd trimester) [26]; Astin et al in 1996 in Malaysia (80% in the 3rd trimester) [27]. However, these results contrast with those obtained by Nyeko et al in Uganda in 2016 (2nd trimester 23.1%, 3rd trimester 20.5%) [23].…”
Section: ) Prevalencesupporting
confidence: 87%
“…These results are similar to those obtained by Aka et al in 2016 in Ivory Coast (100% 3rd trimester) [24], Kamatenesi et al 2007 in Uganda (91% in the 3rd trimester) [26]; Astin et al in 1996 in Malaysia (80% in the 3rd trimester) [27]. However, these results contrast with those obtained by Nyeko et al in Uganda in 2016 (2nd trimester 23.1%, 3rd trimester 20.5%) [23].…”
Section: ) Prevalencesupporting
confidence: 87%
“…Hyper-stimulation of the uterus may also lead to complications such as rupture of the uterus10. Other concerns range from an increased risk of maternal bleeding or impact on neonatal hormones due to the hormonal nature of the herbal medicine611. Decision to use the traditional medicine is most commonly made by grandmothers or mothers and, where mother in-laws are involved, refusal is often very difficult as it would show disrespect6.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, 48.6% (177) participating pregnant women were found to have used CAM in their current pregnancy as at the time of the study (Mekuria, Erku, Gebresillassie, & Birru, 2017). In northern Uganda, the prevalence compared to the study in Ethiopia was less as only 20% (78/383) was found to have used CAM during their current pregnancy (Nyeko, Tumwesigye, & Halage, 2016).…”
Section: Introductionmentioning
confidence: 85%